Blog w kształceniu technicznym - Ciesielka, Marta; Osmenda, Agata; Staśko, Renata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
W artykule zaprezentowano wyniki badań zastosowania blogów w kształceniu technicznym. Przedstawiono analizę porównawczą blogów do zajęć technicznych, opinie nauczycieli blogujących oraz uczniów korzystających i niekorzystających z blogów.

The article presents the results of blogs’ application in technical education. Comparative analysis of blogs for technical education and opinions of blogging teachers as well as pupils using and not using blogs were presented.
Blog in technical education
Keywords: blog; blogosfera; technologia informacyjna; edukacja techniczna; blogosphere; information technology; technical education